Structural basis for nematode eIF4E binding an m(2,2,7)G-Cap and its implications for translation initiation - Liu, Weizhi (Oxford University Press, 2011)
Metazoan spliced leader (SL) trans-splicing generates mRNAs with an m(2,2,7)G-cap and a common downstream SL RNA sequence. The mechanism for eIF4E binding an m(2,2,7)G-cap is unknown. Here, we describe the first structure of an eIF4E with an m(2,2,7)G-cap and compare it to the cognate m(7)G-eIF4E complex. These structures and Nuclear Magnetic Resonance (NMR) data indicate that the nematode Ascaris suum eIF4E binds the two different caps in a similar manner except for the loss of a single hydrogen bond on binding the m(2,2,7)G-cap. Nematode and mammalian eIF4E both have a low affinity for m(2,2,7)G-cap compared with the m(7)G-cap. Nematode eIF4E binding to the m(7)G-cap, m(2,2,7)G-cap and the m(2,2,7)G-SL 22-nt RNA leads to distinct eIF4E conformational changes. Additional interactions occur between Ascaris eIF4E and the SL on binding the m(2,2,7)G-SL. We propose interactions between Ascaris eIF4E and the SL impact eIF4G and contribute to translation initiation, whereas these interactions do not occur when only the m(2,2,7)G-cap is present. These data have implications for the contribution of 5′-UTRs in mRNA translation and the function of different eIF4E isoforms.